83 The coronary artery disease associated gene JCAD regulates hippo signalling in endothelial cells. (June 2018) - Jones, Peter D; Kaiser, Mike; Najafabadi, Maryam Ghaderi; Andrews, Sarah; Rajmohan, Rathinasabapathy; Ye, Shu; Samani, Nilesh; Webb, Tom; Koplev, Simon; Björkegren, Johan; Zhao, Yuqi; Yang, Xia; et al.
Abstract : Genome-wide association studies have associated a large number of loci with coronary artery disease (CAD) risk. The CAD-associated variants at 10 p11.23 fall in JCAD, which encodes an endothelial junction protein. We set out to investigate the function of JCAD in endothelial cells using knockdown of JCAD in comparison to a non-targeting control siRNA. Knockdown of JCAD reduced cellular proliferation by approximately 15% after 48 hours (p=0.0002). A wound healing assay showed approximately 30% reduction in migration in JCAD knockdown cells (p=0.001). Apoptosis of JCAD knockdown cells was increased by approximately 50% compared to control siRNA treated cells (p=0.005). A matrigel tube-formation assay was used to determine the cells angiogenic capability and showed a reduction in tubule length formed of roughly 25% (p=0.0007). To determine if JCAD is involved in regulation of monocyte adhesion we used an in vitro monocyte adhesion assay and found that JCAD knockdown in endothelial cells reduced adhesion by approximately 30% (p=0.0001). JCAD knockdown in endothelial cells also decreased adhesion molecule expression as measured by qPCR – ICAM1 was reduced by around 18% (p=0.022), VCAM1 was reduced by 25% (p=0.008) and SELE was reduced by 22% although this wasn't statistically significant (p=0.092). JCAD has recently been shown to interact with LATS2, a core kinase of the Hippo signalling pathway. We therefore sought to determine if the regulation of endothelial cell function by JCAD occurs via Hippo pathway regulation. We confirmed the physical interaction between JCAD and LATS2 by immunoprecipitation. LATS2 acts via phosphorylation of the Hippo pathway effector YAP which excludes YAP from the nucleus preventing it from promoting target gene expression. We demonstrated increased YAP phosphorylation in cells following JCAD knockdown and by immunofluorescence we showed that JCAD siRNA reduced YAP nuclear/cytoplasmic ratio (p=0.0001). We also detected reduced expression of YAP target genes by qPCR. Using double JCAD and LATS2 siRNA treatments, we have also demonstrated that the regulation of endothelial cell phenotypes by JCAD requires LATS2. Additionally, co-expression analysis of RNA-seq data from normal and atherosclerotic blood vessels found JCAD as a key driver of a module enriched for genes involved in YAP/TAZ signalling, supporting our in vitro findings. We also identified an eQTL for the lead CAD associated SNP at 10 p11.23 with JCAD expression, suggesting that altered transcriptional regulation of JCAD is the causal mechanism at this locus. These data suggest that JCAD encodes a novel regulator of Hippo signalling in endothelial cells and suggest that the variants at the 10 p11.23 CAD locus act through JCAD to increase endothelial cell dysfunction via Hippo signalling.